End-to-End Response Time of 61499 Distributed Applications over Switched Ethernet - Lindgren, Per (2017)
The IEC 61499 standard provides means to specify distributed control systems in terms of function blocks. For the deployment, each device may hold one or many logical resources, each consisting of a function block network with service interface blocks at the edges. The execution model is event driven (asynchronous), where triggering events may be associated with data (and seen as messages). In this paper, we propose a low-complexity implementation technique allowing to assess end-to-end response times of event chains spanning over a set of networked devices. Based on a translation of IEC 61499 to RTFM1 -tasks and resources, the response time for each task in the system at the device-level can be derived using established scheduling techniques. In this paper, we develop a holistic method to provide safe end-to-end response times taking both intra and interdevice delivery delays into account. The novelty of our approach is the accuracy of the system scheduling overhead characterization. While the device-level (RTFM) scheduling overhead was discussed in previous works, the network-level scheduling overhead for switched Ethernets is discussed in this paper. The approach is generally applicable to a wide range of commercial offthe-shelf Ethernet switches without a need for expensive custom solutions to provide hard real-time performance. A behavior characterization of the utilized switch determines the guaranteed response times. As a use case, we study the implementation onto (single-core) Advanced RISC Machine (ARM)-cortex-based devices communicating over a switched Ethernet network. For the analysis, we define a generic switch model and an experimental setup allowing us to study the impact of network topology as well as 802.1Q quality of service in a mixed critical setting. Our results indicate that safe sub millisecond end-to-end resp